COVID-19 vaccine hesitancy between family decision-makers and non-decision-makers among college teachers - Rong Xu; Guifeng Shi; Shuo Zheng; Tao-Hsin Tung; Meixian Zhang (Annals of Medicine, 2023)
AbstractBackground Teachers with high educational levels significantly impact the health-related knowledge and attitudes of young students and their family members. This study aimed to investigate the coronavirus disease 2019 (COVID-19) vaccine hesitancy and associated factors, and compare the differences between decision-makers and non-decision-makers among college teachers.Methods A cross-sectional online survey was administered across mainland China from 4 to 7 August 2021. Overall, 251 college teachers were included using snowball sampling. A multivariable logistic regression model was applied to explore the association between decision-makers and hesitancy to receive a COVID-19 vaccine.Results Overall, 42.2% of the teachers were hesitant to being vaccinated against COVID-19. The hesitancy rate was lower among primary decision-makers than that among non-decision-makers (34.8% vs. 60.3%, p < .001). Primary decision-makers were less hesitant regarding COVID-19 vaccination than non-decision-makers (OR = 0.37, 95% CI 0.20–0.70); remarkably, whereas those engaged in nursing education versus non-medical related professional education (OR = 2.67, 95% CI 1.29–5.49), and partial versus full-course vaccination recipients (OR = 4.48, 95% CI: 1.76–11.42) were more likely to be hesitant regarding COVID-19 vaccination.Conclusion Our findings indicate that a high proportion of college teachers in China are hesitant to receiving COVID-19 vaccination, and that primary decision-makers are less likely to exhibit hesitancy to being vaccinated against COVID-19 than non-decision-makers in their family. Family decision-makers among teachers can be considered a priority for COVID-19 vaccine promotion, thereby enhancing vaccine acceptance among vulnerable populations—including older adults and children—and preventing adverse outcomes.KEY MESSAGESQuestion: How prevalent is COVID-19 vaccine hesitancy among college teachers? Do differences exist between decision-makers and non-decision-makers?Findings: We found that a substantial proportion of college teachers are hesitant to being vaccinated against COVID-19, and that family decision-makers exhibited a lower hesitancy rate than non-decision-makers.Meaning: Our findings indicate that distinguishing between family decision-makers and non-decision-makers is necessary to facilitate vaccination promotion interventions among college teachers.